PERAN ORANGTUA DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Nadira; Ikrami, Nurul; Adrias; Azmi Alwi, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Elementary school students’ learning motivation is closely related to the formation of learning patterns and habits in their daily lives. A review of various studies indicates that students’ learning habits are not yet optimally formed, characterized by low learning engagement, a lack of consistency in completing assignments, and minimal learning initiative. This condition is influenced by external factors, particularly parental involvement in supporting their children’s learning process. This study aims to describe the role of parents in shaping learning motivation, as reflected in elementary school students’ learning patterns and habits, and to analyze their relationship to student learning outcomes. This study used a qualitative approach using library research. Data analysis was conducted using content analysis, grouping findings based on specific themes. The study results indicate that parental roles, such as attention to learning activities, implementation of parenting styles, providing support, and supervising learning, contribute to the formation of more structured and consistent learning habits in students. Positively formed learning habits have implications for increased learning motivation and student learning outcomes. Thus, parental involvement plays a significant role in shaping elementary school students’ learning patterns and habits.